2012
DOI: 10.1371/journal.pone.0049239
|View full text |Cite
|
Sign up to set email alerts
|

BG7: A New Approach for Bacterial Genome Annotation Designed for Next Generation Sequencing Data

Abstract: BG7 is a new system for de novo bacterial, archaeal and viral genome annotation based on a new approach specifically designed for annotating genomes sequenced with next generation sequencing technologies. The system is versatile and able to annotate genes even in the step of preliminary assembly of the genome. It is especially efficient detecting unexpected genes horizontally acquired from bacterial or archaeal distant genomes, phages, plasmids, and mobile elements. From the initial phases of the gene annotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…In the area of prokaryotic genome annotation, existing NGS-related studies 11 have focussed on the possibly increased level of sequencing errors associated with such technologies. Here, we showed that the quality of the Sm2011 genomic sequence obtained by NGS is comparable with, if not better than, the Sm1021 genomic sequence previously generated by Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the area of prokaryotic genome annotation, existing NGS-related studies 11 have focussed on the possibly increased level of sequencing errors associated with such technologies. Here, we showed that the quality of the Sm2011 genomic sequence obtained by NGS is comparable with, if not better than, the Sm1021 genomic sequence previously generated by Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent sequencing of bacterial and archeal genomes, the annotation has still been done manually owing to the lack of appropriate tools to integrate RNA-Seq data. 5 Indeed, most existing prokaryotic gene finders 69 or high-level bacterial annotation systems 10,11 are based on genomic sequence analysis and cannot take into account available expression data in the structural prediction. Expert annotation using RNA-Seq data has been recently facilitated by the use of integrated tools, such as VESPA 12 or MicroScope, 13 which allow to simultaneously visualize genomic, transcriptomic, proteomic or syntenic data, but the ultimate curation process still remains laborious.…”
Section: Introductionmentioning
confidence: 99%
“…The assemblies were done using high values for k parameter to reduce the possibility of misassembles. The prediction of genes and the functional annotation was carried out using BG7 [29]. A de novo assembly was carried out using Velvet [28].…”
Section: Methodsmentioning
confidence: 99%
“…The microbial genomics community around the world immediately took up the challenge to study the organism collaboratively (a process that was dubbed by some bloggers as the first "Tweenome"). Using these data, within the first 24 h of release, researchers from Birmingham University had released their own genome assembly in the same manner, and a group in Spain released analyses from a new annotation platform and set up a collaborative GitHub repository to provide a home to these analyses and data [58]. Within days of the initial release, a potential ancestral strain had been identified by a blogger in the US [51], helping clear Spanish farmers of the blame.…”
Section: The 2011 E Coli 0104:h4 Outbreak Genome: Fighting Disease Omentioning
confidence: 99%